the STUDENT ACADEMIC STRESS IN IMPLEMENTING ONLINE LEARNING DURING THE COVID-19 PANDEMIC IN MAN 1 JEMBER - weni kurnia rahmawati (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2021)
The goals to be accomplished in this review are: To discover how much scholastic pressure is capable by understudies in web based learning circumstances during the Covid-19 pandemic. This review utilizes a quantitative elucidating strategy. The populace in this review were all understudies of MAN 1 Jember. The quantity of populace considered is from the standard class. In particular studying Language, Mathematics and Natural Sciences and Social Sciences. A sum of 760 understudies. In this review, the testing procedure utilized was proportionate delineated arbitrary examining with a sum of 114 understudies. Strategies for information assortment utilizing a poll. Test the instrument utilizing legitimacy and dependability. Information examination utilized unmistakable insights. In view of the aftereffects of exploration and conversation, it is realized that the anxiety of understudies during web based getting the hang of during the COVID-19 pandemic is high. A large portion of the feelings of anxiety of understudies in the medium classification were 67%, while the understudies were 16% in the low class and 17% in the high classification.